Green and High Throughput Assay Using 96-Microwell Base to Determine Metformin Hydrochloride in the Tablet Dosage Form - Mohammed Alqarni; Atheer Alshehri; Bayan Almalki; Refah Althumali; Maram Alghamdi; Rawan Alqahtani; Safia G. Alotibi; Ali Alqarni; Adel H. Awad; Ibrahim A. Naguib (International Journal of Analytical Chemistry)
Metformin (MET) is an oral antidiabetic drug widely used as the primary treatment for type 2 diabetes mellitus (T2DM). While various spectrophotometric assays exist for determining MET in pharmaceutical formulations, they often have limited throughput for quality control purposes. This study describes the validation of a 96-microwell plate spectrophotometer method using charge-transfer complexes (CTCs) with chloranilic acid (CLA) and 2,3-dichloro-5,6-dicyano-1,4-benzoquinone (DDQ) for the quality control and detected of MET. This reaction was carried out in 96-microwell plates, and the absorbance of the colored complexes of CLA and DDQ were measured at 530 nm and 460 nm, respectively, using an absorbance microplate reader. This study aims to identify and quantify the use of a 96-microwell plate spectrophotometer analytical technique for assessing complicated formulations. The method was successfully used for the quantification of MET in the tablet dosage form. The results showed good correlation coefficients (0.996 and 0.997) with CLA and DDQ, respectively. The present method showed high precision with RSD % not exceeding 2.17%. The accuracy of the method was obtained by recovery percentage, with percentage values less than ±5%. The Analytical Greenness Metric (AGREE) was used to evaluate greenness of the assays. The result show that the microwell assay method is greenness and suitable for handling large samples on a daily used with high throughput analysis. The use of the 96-microwell-plate method is superior to the existing method in terms of simplicity of the procedure, the low economic cost, and its consumption of low amounts of reagents and organic ethanol solvent, making it an environmentally friendly method. Therefore, these advantages make them suitable and rapid alternatives method to current methods for routine metformin analysis in quality control laboratories.